An Optimal Fourth Order Iterative Method for Solving Nonlinear Equations and Its Dynamics. (5th November 2015) - Sharma, Rajni; Bahl, Ashu
Abstract : We present a new fourth order method for finding simple roots of a nonlinear equationf ( x ) = 0 . In terms of computational cost, per iteration the method uses one evaluation of the function and two evaluations of its first derivative. Therefore, the method has optimal order with efficiency index 1.587 which is better than efficiency index 1.414 of Newton method and the same with Jarratt method and King's family. Numerical examples are given to support that the method thus obtained is competitive with other similar robust methods. The conjugacy maps and extraneous fixed points of the presented method and other existing fourth order methods are discussed, and their basins of attraction are also given to demonstrate their dynamical behavior in the complex plane.